1993
DOI: 10.1161/01.hyp.21.3.267
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in calcium metabolism in young people at risk for primary hypertension. The Dutch Hypertension and Offspring Study.

Abstract: Several disturbances in calcium metabolism have been reported in primary hypertensive subjects. It is, however, not clear whether these alterations predate the development of hypertension or occur as a consequence of high blood pressure. We studied indexes of calcium metabolism in three groups of normotensive children with different familial predispositions for hypertension, based on parental blood pressure levels, with two, one, or no hypertensive parents. Plasma intact parathyroid hormone pressure regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 32 publications
1
14
0
1
Order By: Relevance
“…Considerable evidence exists that calcium plays a central role in the regulation of vascular smooth muscle contraction and there is growing evidence in human and animal studies that alterations of calcium metabolism at either the systemic or cellular level may be involved in the pathogenesis of hypertension (26)(27)(28)(29). Moreover, similar alterations in calcium metabolism have been found in the normotensive offspring of hypertensive parents suggesting that they may be genetically determined (30). Of more direct relevance to the findings here, high calcium diet and parathyroidectomy in LH rats influence blood pressure and vascular reactivity (31,32).…”
Section: Discussionsupporting
confidence: 77%
“…Considerable evidence exists that calcium plays a central role in the regulation of vascular smooth muscle contraction and there is growing evidence in human and animal studies that alterations of calcium metabolism at either the systemic or cellular level may be involved in the pathogenesis of hypertension (26)(27)(28)(29). Moreover, similar alterations in calcium metabolism have been found in the normotensive offspring of hypertensive parents suggesting that they may be genetically determined (30). Of more direct relevance to the findings here, high calcium diet and parathyroidectomy in LH rats influence blood pressure and vascular reactivity (31,32).…”
Section: Discussionsupporting
confidence: 77%
“…Abnormal calcium transport has been associated with essential hypertension (39). DeFronzo et al (13,14) reported that insulin might act on renal distal tubules to enhance calcium excretion in humans, promote cellular uptake of phosphate and enhance tubular reabsorption of phosphate at the proximal and distal tubules in dogs.…”
Section: Fig 4 Correlation Between Serum Intact Parathyroid Hormonementioning
confidence: 99%
“…Normotensive offspring of hypertensive patients also have disturbed Ca 2ϩ metabolism, suggesting a possible genetic basis for these abnormalities (9,10). We previously reported familial aggregation of hypertension in patients with KSD and hypercalciuria and hyperuricosuria but not with either urinary abnormality alone (11,12).…”
mentioning
confidence: 99%